2016
DOI: 10.1155/2016/2678269
|View full text |Cite
|
Sign up to set email alerts
|

Power Adaptive Data Encryption for Energy-Efficient and Secure Communication in Solar-Powered Wireless Sensor Networks

Abstract: Basic security of data transmission in battery-powered wireless sensor networks (WSNs) is typically achieved by symmetric-key encryption, which uses little energy; but solar-powered WSNs sometimes have sufficient energy to achieve a higher level of security through public-key encryption. However, if energy input and usage are not balanced, nodes may black out. By switching between symmetric-key and public-key encryption, based on an energy threshold, the level of security can be traded off against the urgency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Encryption of WSNs is usually divided into symmetric key based algorithms and public key based algorithms. WSNs usually use symmetric key based algorithms which have weak crypto strengths compared to high energy efficiency, and public key algorithms that require a lot of energy to provide high crypto strengths [64].…”
Section: A Data Confidentialitymentioning
confidence: 99%
“…Encryption of WSNs is usually divided into symmetric key based algorithms and public key based algorithms. WSNs usually use symmetric key based algorithms which have weak crypto strengths compared to high energy efficiency, and public key algorithms that require a lot of energy to provide high crypto strengths [64].…”
Section: A Data Confidentialitymentioning
confidence: 99%
“…However, the process to find trusted nodes to perform the encryption and to maintain the integrity and authenticity of the data is itself a very challenging task to perform at end nodes. Power adaptive encryption is introduced for solar-powered wireless sensor networks in [52]. The technique switches between symmetric and public-key cryptography depending on the urgency of energy saving in the node.…”
Section: Security Vulnerabilities In Lpwanmentioning
confidence: 99%
“…In general, using private-key cryptography for data encryption is not a time-consuming process, and thus expends less energy than public-key cryptography. For example, the experimental results from Kim et al [27] showed that a public-key algorithm named the elliptic curve integrated encryption scheme (ECIES) consumes a thousand times more energy during the encryption process than the popular AES-128 private-key method. Even though a public-key algorithm can increase the security level by sacrificing a huge amount of energy, it is not a favorable choice for many wireless systems like CRNs.…”
Section: System Modelmentioning
confidence: 99%